2020
DOI: 10.1155/2020/5341247
|View full text |Cite
|
Sign up to set email alerts
|

CD147 Aggravated Inflammatory Bowel Disease by Triggering NF‐κB‐Mediated Pyroptosis

Abstract: Background. Pyroptosis, a novel form of inflammatory programmed cell death, was recently found to be a cause of mucosal barrier defect. In our pervious study, CD147 expression was documented to increase in intestinal tissue of inflammatory bowel disease (IBD). Objective. The aim of this study was to determine the function of serum CD147 in pyroptosis. Methods. The study group consisted of 96 cases. The centration of CD147,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…CD147 also serves as a novel receptor on platelets that activates platelets and aggravates inflammation in monocytes ( Schmidt et al, 2008 ). Several studies have shown that CD147 is strongly involved in the development of various inflammatory diseases, such as COVID-19 ( Wang et al, 2020 ), rheumatoid arthritis ( Guo et al, 2019 ), and inflammatory bowel disease ( Xu et al, 2020 ). Our previous studies have shown that CD147 participates in reprogramming of glucose metabolism ( Huang et al, 2014 ) as well as in lipid metabolism ( Li J. et al, 2015 ) in hepatocellular carcinoma, including de novo lipogenesis and fatty acid-oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…CD147 also serves as a novel receptor on platelets that activates platelets and aggravates inflammation in monocytes ( Schmidt et al, 2008 ). Several studies have shown that CD147 is strongly involved in the development of various inflammatory diseases, such as COVID-19 ( Wang et al, 2020 ), rheumatoid arthritis ( Guo et al, 2019 ), and inflammatory bowel disease ( Xu et al, 2020 ). Our previous studies have shown that CD147 participates in reprogramming of glucose metabolism ( Huang et al, 2014 ) as well as in lipid metabolism ( Li J. et al, 2015 ) in hepatocellular carcinoma, including de novo lipogenesis and fatty acid-oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer, CD147 interacted with a variety of proteins, induces the secretion of MMPs, and promoted tumor invasion and metastasis [129,[133][134][135][136]. Recent studies have shown that CD147 was significantly increased in intestinal mucosa of IBD patients and aggravated IBD inflammatory response by activating NF-κB [137]. This indicates the important significance of CD147 in inflammatory diseases, and further confirms the results of previous studies [116][117][118][119][120][121][122][123][124] that eCypA firstly bound to CD147 on cell surface, and activated multiple signal pathways to regulate inflammatory cells, then promoted the expression of MMPs and other factors that can promote the occurrence and development of inflammation such as IBD, expecially UC.…”
Section: Cypamentioning
confidence: 99%
“…At present, a compelling body of evidence supports the fact that increased sRAGE levels correlate with a decrease in the RAGE activation-mediated inflammatory responses in many clinical entities[ 60 - 63 ]. In this context, it is important to highlight that CD147 significantly contributes to epithelial inflammation in many clinical entities including IBD[ 64 , 65 ], and it has been recently shown to act as a receptor for SARS-CoV-2[ 66 ]. Noteworthy, the inhibition of RAGE activation-mediated inflammatory response leads to a reduced expression of CD147[ 67 ].…”
Section: Rage Axis Activation In Ibdmentioning
confidence: 99%